Menumbuhkan Kesehatan Mental Pada Anak Melalui Permainan Tradisional - Saputra, Kosasih Adi; Tandiana, Soni Tantan; Andrias, Mohammad Ali; Saepulmilah, Ceceng; Ridwan, Thaufan Abiyuna (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Children today experience two things that have the potential to affect mental health, namely, first, dependence on technology, especially mobile phones as a means of playing. Second, forgetting traditional games that are healthier, and can preserve culture with materials provided by nature and the environment. Mental health is an important aspect in realizing comprehensive health. This activity reintroduces traditional games, such as Gatrik, stilts/jajangkungan, boyboyan, and clogs. This is beneficial for the community, the existence of higher education institutions to educate the community regarding the importance of fostering children's mental health also requires other nuances in the children's play environment. No less important is the assistance of parents and the local environment to continue to create a friendly environment for children, children need facilities to play freely.